2020
DOI: 10.3390/su12125187
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into Stakeholders’ Perception of Smart Campus Criteria: The American University of Sharjah as a Case Study

Abstract: In recent times, smart cities and sustainable development have drawn significant research attention. Among developed and developing countries, the United Arab Emirates (UAE) has been at the forefront in becoming an incubator for smart cities; in particular, it has placed some efforts in the education sector by transforming the traditional campus into a Smart Campus. As the term Smart Campus attracts professionals and academics from multiple disciplines, and the technology keeps intervening in every aspect of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…It is generally believed that in the current scenario, quick transformation is vital for educational sustainability, but Valverde observed that numerous risks are also associated with digital learning [17]. On the other hand, Vian et al proposed the idea of a smart campus to harness the integration of information and communications technology (ICT) applications with adaptive learning [18]. Conversely, Di Pietro found that students with overseas study experience had a better chance of gaining employment due to better adaptability, multicultural experience, bilingual skills and dealing with unexpected situations [19].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally believed that in the current scenario, quick transformation is vital for educational sustainability, but Valverde observed that numerous risks are also associated with digital learning [17]. On the other hand, Vian et al proposed the idea of a smart campus to harness the integration of information and communications technology (ICT) applications with adaptive learning [18]. Conversely, Di Pietro found that students with overseas study experience had a better chance of gaining employment due to better adaptability, multicultural experience, bilingual skills and dealing with unexpected situations [19].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the outcome of each archetype described in the subsection below can be transferred to many campuses in developing countries where holistic Smart Campus transitions are at embryonic phases due to lack of awareness and knowledge. This challenge is further exacerbated by the lack of relevant literature detailing the evidence of successful holistic Smart Campus transitions and/or guidelines for achieving same, globally [23]. This is a gap where this study seeks to make a salient contribution towards bridging.…”
Section: Nz-exp1mentioning
confidence: 99%
“…Although these transitions are on-going, there is little evidence to show that the views of the users are being incorporated during the decision-making processes which govern its conceptualization, design, and implementation stages [23]. Scholars have observed the unidirectional nature of the Smart City implementation programs [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Precision teaching based on big data applications and artificial intelligence technology is used as a vital standard to measure the education's efficiency and as a guideline to create interactive and productive learning in classrooms [9]. Smart learning could encourage innovative talents among students [10] and boost their learning quality by creating time-efficient, interactive, sustainable, userfriendly, and cooperative surroundings [11]. The campus with a conducive learning environment will provide lecturers multitude of resources to deliver their knowledge to the students.…”
Section: A Smart Learningmentioning
confidence: 99%